Adult Lead Poisoning Caused by Contaminated Opium: A Two-Year Longitudinal Follow-Up Study - Malihe-Sadat Hosseini; Amir Salimi; Scott Phillips; Nasim Zamani; Hossein Hassanian-Moghaddam (Ubiquity Press, 2021)
Background: A major episode of lead poisoning caused by lead-adulterated opium occurred in Iran in 2016. Patients were removed from exposure and treated with chelating agents. A subset of those patients was evaluated in this follow-up study to evaluate treatment efficacy in relation to patient outcome. Methods: Between March 2016 and December 2017, thirty-five male cases of lead poisoning due to ingestion of lead-adulterated opium were followed for two years. There are three patient groups: 1) those who abstained from opium use; 2) those who continued to use potentially contaminated opium; and 3) those who abstained from opium and were placed on maintenance therapy. Maintenance therapy included: methadone and opium tincture, offered by the Opioid Maintenance Therapy (OMT) clinics. Amongst the three patient groups Blood Lead Levels (BLL), complete blood count, and kidney and liver function tests were compared. Findings: The results of BLL, hemoglobin, hematocrit, and aspartate aminotransferase were significantly different between the admission time and follow-up. Of the three patient groups, no difference was detected in these measures. Conclusions: Treatment of lead poisoning combined with OMT proved an effective method to prevent recurrent lead poisoning.